2015
DOI: 10.1371/journal.pone.0128175
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Melanopsin Photoreception and Antagonism of the Histamine H3 Receptor by Ciproxifan Inhibit Light-Induced Sleep in Mice

Abstract: Light has direct effects on sleep and wakefulness causing arousal in diurnal animals and sleep in nocturnal animals. In the present study, we assessed the modulation of light-induced sleep by melanopsin and the histaminergic system by exposing mice to millisecond light flashes and continuous light respectively. First, we show that the induction of sleep by millisecond light flashes is dose dependent as a function of light flash number. We found that exposure to 60 flashes of light occurring once every 60 secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Light has direct effects on sleep and wakefulness causing arousal in diurnal animals and sleep in nocturnal animals. Histaminergic neurotransmission attenuates the light-induced sleep response during the dark period [ 18 ]. Using knockout (KO) mice lacking HDC, Parmentier et al [ 19 ] demonstrated the importance of histaminergic neurons in maintaining wakefulness under behavioral challenges.…”
Section: Compartmentalization and Physiological Functionsmentioning
confidence: 99%
“…Light has direct effects on sleep and wakefulness causing arousal in diurnal animals and sleep in nocturnal animals. Histaminergic neurotransmission attenuates the light-induced sleep response during the dark period [ 18 ]. Using knockout (KO) mice lacking HDC, Parmentier et al [ 19 ] demonstrated the importance of histaminergic neurons in maintaining wakefulness under behavioral challenges.…”
Section: Compartmentalization and Physiological Functionsmentioning
confidence: 99%
“…Mouse ex vivo analysis revealed that retinal photoreceptors are required to encode flashes, and are not diminished by knocking out melanopsin [ 30 ]. Sleep induction of mice by flashes is reduced, but not obviated by melanopsin’s absence [ 35 ]. The multiplexing of light information through mechanisms of different sensitivity may optimally identify lighting changes that are environmentally significant, such as the timing of dawn and dusk [ 30 ].…”
Section: Discussionmentioning
confidence: 99%